(untitled) (International relations and international law Journal, 2024)
The migration process from China to Kazakhstan is complex, poorly understood, and requires a variety of theoretical and methodological approaches to fully understand its dynamics. For this purpose, this paper applies theories of international migration to gain a better understanding of the movement of migrants between the two countries. The study focuses on macro-level migration theories to identify the political and economic implications of migration in the context of Kazakhstan-China relations. The study highlights the need for integrated methods, including both qualitative and quantitative approaches such as surveys, interviews, and case studies, to capture the multifaceted nature of migration. It also highlights the need for improved data collection methods and suggests that a combination of administrative data, expert assessments, and sample surveys can provide a more accurate understanding of illegal migration. The paper pays particular attention to irregular migration, given the high numbers of migrants from PRC to Kazakhstan, primarily for economic reasons. Thus, the paper attempts to map out the dynamics of Chinese-Kazakh migration by highlighting its history, development, sources, and factors, using findings from Western and domestic scholars. Key words: migration, neoclassical theory, macro-level theory, theory of new economics of migration, theory of migration networks, global migration.